Angiotensin Converting Enzyme (ACE) Inhibitory Peptides: Production and Implementation of Functional Food - De Leo, F.; Panarese, S.; Gallerani, R.; Ceci, L. R. (Current Pharmaceutical Design, 2009)
In recent decades, the most successful strategy for controlling blood pressure has been inhibition of the angiotensin-converting enzyme (ACE). ACE inhibitors of chemical synthesis (captopril, enalapril, ramipril and trandolapril) have been widely used clinically to reduce mortality in patients with heart failure, and in patients with recent myocardial infarction and heart failure or marked left ventricular dysfunction. In addition to preventive and therapeutic drugs, increased attention has been paid to identifying dietary compounds that may contribute to cardiovascular treatment and prevention. ACE inhibitory peptides, derived from a multitude of plant and animal proteins such as milk, soy or fish, represent sources of health-enhancing components. These ACE inhibitory peptides can be enzymatically released from precursor proteins in vitro and in vivo, respectively during food processing and gastrointestinal digestion. They have shown the ability to lower blood pressure by limiting the vasoconstrictory effects of Angiotensin II and potentiating the vasodilatory effects of Bradykinin. By using specific procedures they may be generated in or incorporated into functional foods for the development of ‘natural’ beneficial health products. Several products containing peptides with ACE inhibitory properties are currently on the market or in development. This review focuses on the use, application and future perspective of bioactive peptides with properties relevant to cardiovascular health.
Keywords: angiotensin converting enzyme inhibitory peptides